Maternal Work–Family Conflict and Psychological Distress: Reciprocal Relationships Over 8 Years. Issue 1 (9th November 2015) - Westrupp, Elizabeth M.; Strazdins, Lyndall; Martin, Angela; Cooklin, Amanda; Zubrick, Stephen R.; Nicholson, Jan M.
Abstract : The relationships between employed mothers' work–family conflict and psychological distress are unlikely to be static or one way. Using longitudinal data, the authors investigated reciprocal effects between work–family conflict and psychological distress across 8 years of the family life cycle. They modeled cross‐lagged structural equations over 5 biennial waves of data, in 4 overlapping samples of Australian mothers reentering work between child ages 0–1 to 8–9 ( N range: 1, 027–2, 449). The findings revealed that work–family conflict and psychological distress are distinctive aspects of mothers' well‐being that influence each other over time. Reciprocal influences were not confined to one period of parenting but continued as children grew older. Associations persisted after controlling for a range of work and family characteristics, and there was no evidence of mediation by family socioeconomic status, maternal age, or job quality. The findings suggest that employed mothers may benefit from policies and workplace practices that both promote maternal well‐being and reduce conflicts between employment and raising children.